Preparation method of F and N co-doped NaFePO4 / C electrode material
Through the solid -phase and short -term planet ball grinding technology, the FD and N co -doped NaFepo4/C materials solved the problem of insufficient electrochemical performance of iron -sodium -sodium iron phosphate -type iron phosphate, and achieved high ratio and low cost Preparation of battery materials.
Patent Information
- Application Number
- CN202411335615.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-21
AI Technical Summary
The existing iron phosphate sodium phosphate battery materials lack sodium phosphate diffusion channels in the structure, and the electrochemical performance cannot meet the application needs. The modification methods such as high-energy ball milling and sol-gel methods have high cost and high energy consumption or Problems with complex preparation process.
The solid-phase method and short-time planetary ball milling process are used to synthesize F and N co-doped NaFePO4/C materials through anion doping, which significantly improves the specific capacity of the material.
Improving the capacity and electrochemical properties of materials, reducing the cost and energy consumption of preparation, simplifying the process, and suitable for large -scale production.
Smart Images

Figure CN119330321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a F and N co-doped NaFePO4 / C electrode material, belonging to the field of electrochemistry and new energy materials. Background Art
[0002] With the rapid development of the world economy, lithium-ion batteries (LIBs), as efficient energy storage battery devices, have achieved rapid development in various fields such as electric vehicles, wearable devices and electrochemical energy storage. However, due to the low global reserves and uneven distribution of lithium resources, rising costs and poor safety, lithium-ion batteries are difficult to meet large-scale energy storage applications. Therefore, sodium-ion batteries, which have the same working principle as lithium-ion batteries, have received widespread attention. Polyanion materials in sodium-ion battery cathode materials are considered to be one of the most promising sodium-ion battery cathode materials because of their stable structure, low preparation cost and suitability for large-scale production. Among them, sodium iron phosphate materials have become a hot spot in the research of sodium-ion battery cathode materials because of their simple preparation process, low cost and green environmental protection. Sodium iron phosphate materials are divided into olivine type and pyrophosphate type. Olivine type sodium iron phosphate is mainly prepared by ion exchange, which has high preparation cost and complex process and is not suitable for large-scale production. In contrast, the synthesis process of pyrophosphate type sodium iron phosphate is relatively simple, which has attracted great interest from researchers. However, due to the lack of sodium ion diffusion channels in the material structure, its electrochemical performance cannot meet application requirements. It is reported that methods such as amorphization, structural design, ion doping, carbon composite, nano-sizing and sol-gel can improve the electrochemical performance of pyrophosphate-type sodium iron phosphate. However, among the currently effective modification methods, amorphization is achieved by high-energy ball milling for 15-24 hours, and sol-gel method combined with subsequent long-term (>9 hours) planetary ball milling to increase the specific capacity of the material by adding additional sodium ion diffusion paths, but high-energy ball milling equipment is expensive and energy-intensive; while sol-gel method is time-consuming, and subsequent long-term planetary ball milling will also increase the material preparation cost. Structural design is to design the sodium iron phosphate material into a porous or hollow nanomaterial to increase the specific capacity by providing additional active sites, but this method usually uses organic solvents with certain toxicity, which is costly, complicated in preparation process, and not environmentally friendly. Nano-materials use hydrothermal, sol-gel and electrospinning processes to increase the specific capacity by shortening the diffusion path of sodium ions and increasing the migration rate of sodium ions. However, the hydrothermal method has low output, high equipment requirements and poor safety; the electrospinning process has high production costs and is greatly affected by the environment; the sol-gel method is time-consuming, and long-term planetary ball milling will also increase the material preparation cost. In particular, the tap density of nanomaterials is usually low, which is not conducive to the improvement of energy density. It can be seen that the preparation process of the above method is complicated and not easy to scale production. The present invention adopts a solid phase method, uses a short-time planetary ball milling process, and synthesizes a F and N co-doped NaFePO4 / C material through anion doping, which significantly improves the specific capacity of the material. Using it as the positive electrode of a sodium ion battery, it shows high capacity and has great potential application value. Summary of the invention
[0003] The raw materials involved in the present invention are sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, citric acid, urea and NaBF4. Through solid phase mixing and step-by-step calcination reaction, F and N co-doped NaFePO4 / C material is obtained. In the material preparation process, sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, citric acid, urea and F source (one of ammonium fluoride, sodium fluoride and sodium tetrafluoroborate) are uniformly mixed in a ball mill, ball milled after adding a solvent, dried, and calcined in two steps in a protective atmosphere to obtain F and N co-doped NaFePO4 / C material.
[0004] Compared with the prior art, the present invention has the following significant features: (1) The raw material cost of the present invention is low, the preparation process is simple, and it is easy to mass produce.
[0005] (2) The F and N co-doped NaFePO4 / C material obtained by the present invention has good crystallinity, which is beneficial to improving the electrical conductivity of the material and the energy density of the battery, ensuring batch consistency, and improving the battery life.
[0006] (3) The prepared F and N co-doped NaFePO4 / C material exhibits the best electrochemical performance when urea is selected as the N source and sodium tetrafluoroborate is selected as the F source. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 These are the XRD patterns of the samples prepared in Example 1, Example 2, Example 7, Example 8, Example 9, and Example 10.
[0008] Figure 2 These are the first three charge-discharge curves of the sample prepared in Example 1.
[0009] Figure 3 These are the first three charge and discharge curves of the sample prepared in Example 2.
[0010] Figure 4 These are the first three charge and discharge curves of the sample prepared in Example 3.
[0011] Figure 5 These are the first three charge and discharge curves of the sample prepared in Example 4.
[0012] Figure 6 These are the first three charge and discharge curves of the sample prepared in Example 5.
[0013] Figure 7 These are the first three charge and discharge curves of the sample prepared in Example 6.
[0014] Figure 8 These are the first three charge and discharge curves of the sample prepared in Example 7.
[0015] Fig. 9These are the first three charge and discharge curves of the sample prepared in Example 8.
[0016] Fig.10 These are the first three charge-discharge curves of the sample prepared in Example 9.
[0017] Fig.11 These are the first three charge-discharge curves of the sample prepared in Example 10. DETAILED DESCRIPTION
[0018] A method for preparing a F and N co-doped NaFePO4 / C electrode material comprises the following steps: uniformly mixing sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, citric acid, a N source and a F source, adding a solvent and performing ball milling, and then drying and calcining in a protective atmosphere in two steps to prepare the F and N co-doped NaFePO4 / C electrode material.
[0019] The N source is urea, and the F source is one of ammonium fluoride, sodium fluoride and sodium tetrafluoroborate. The molar percentage of the selected F source in diammonium phosphate is 1-10%, and the selected N source accounts for 5-15% of the total mass of sodium carbonate, ferrous oxalate, diammonium phosphate and the F source.
[0020] The molar percentage of the selected F source in diammonium phosphate is 1-10%, and the molar percentage of the selected N source in the total mass of sodium carbonate, ferrous oxalate, diammonium phosphate and the F source is 5-15%.
[0021] The N source is selected from urea; the F source is selected from any one of ammonium fluoride, sodium fluoride and sodium tetrafluoroborate.
[0022] In some preferred embodiments, the fluorine source is selected from sodium tetrafluoroborate.
[0023] In some preferred embodiments, the amount of fluorine source added is The molar ratio of sodium carbonate to ferrous oxalate is 1:2-3.
[0024] In the step, the ball mill speed is 350-400 rpm, and the ball milling time is 3-5 h.
[0025] In the first step, the sintering temperature is 300-350°C and the time is 3-6 h, and the second step, the sintering temperature is 600-650°C and the time is 10-14 h.
[0026] The F and N co-doped NaFePO4 / C electrode material prepared by the method has peaks at characteristic positions of about 12.6°, 26.6°, 30.1°, 32.8°, 33.0°, 34.7°, and 35.5° in the XRD diffraction spectrum.
[0027] The present invention also provides a F, N co-doped NaFePO4 / C electrode sheet, which is prepared by mixing the F, N co-doped NaFePO4 / C electrode material with acetylene black and polyvinylidene fluoride into slurry, coating the slurry on aluminum foil, and then drying, punching and laminating the slurry.
[0028] A positive electrode material comprises the F and N co-doped NaFePO4 / C electrode material.
[0029] A sodium ion battery positive electrode material comprises the F and N co-doped NaFePO4 / C electrode material.
[0030] Example 1 Sodium carbonate, ferrous oxalate, and ammonium dihydrogen phosphate were mixed in a molar ratio of 0.5:1:1, and the amount of citric acid added was 10% of the total mass of sodium carbonate, ferrous oxalate, and ammonium dihydrogen phosphate. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried, calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C. Figure 1 This is the XRD pattern of the sample prepared in Example 1. It can be seen that the XRD pattern of the sample obtained in Example 1 is completely consistent with that of the standard NFP phase (PDF#89-0816), indicating that the sample is NFP. Figure 2 The sample obtained in Example 1 was charged at 0.1 C (1 C = 155 mAh g -1 ) shows the charge and discharge curves of the first three cycles. It can be seen that the first cycle discharge capacity is only 78.6 mAh g -1 .
[0031] Example 2 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F were prepared in a molar ratio of 5:10:9.7:0.3, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (sintering under N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-A3FN. Figure 1 This is the XRD pattern of the sample prepared in Example 2. It can be seen that the XRD pattern of the sample obtained in Example 2 is basically consistent with the standard NFP phase (PDF#89-0816), indicating that the main phase of the sample is NFP. Figure 3 The sample obtained in Example 2 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge-discharge curves of the first three cycles show that the first cycle discharge capacity is 117.3 mAh g -1 .
[0032] Example 3 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F were prepared in a molar ratio of 5:10:9.4:0.6, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-A6FN. Figure 4 The sample obtained in Example 3 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the first cycle discharge capacity is 91.5 mAh g -1 .
[0033] Example 4 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F were prepared in a molar ratio of 5:10:9.1:0.9, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NH4F, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-A9FN. Figure 5 The sample obtained in Example 4 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the discharge capacity of the first cycle is only 65 mAh g -1 .
[0034] Example 5 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF were prepared in a molar ratio of 5:10:9.7:0.3, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-B3FN. Figure 6 The sample obtained in Example 5 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the discharge capacity of the first cycle is only 58.7 mAh g -1 .
[0035] Example 6 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF were prepared in a molar ratio of 5:10:9.4:0.6, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-B6FN. Figure 7 The sample obtained in Example 6 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the first cycle discharge capacity is 80.4 mAh g -1 .
[0036] Example 7 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF were prepared in a molar ratio of 5:10:9.1:0.9, citric acid was added in an amount of 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaF, and urea was added in an amount of 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-B9FN. Figure 1 This is the XRD pattern of the sample prepared in Example 7. It can be seen that the XRD pattern of the sample obtained in Example 7 is basically consistent with the standard NFP phase (PDF#89-0816), indicating that the main phase of the sample is NFP. Figure 8 The sample obtained in Example 7 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the first cycle discharge capacity is 83.1 mAh g -1 .
[0037] Example 8 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4 were prepared in a molar ratio of 5:10:9.7:0.225, the amount of citric acid added was 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4, and the amount of urea added was 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-C3FN. Figure 1 This is the XRD pattern of the sample prepared in Example 8. It can be seen that the XRD pattern of the sample obtained in Example 8 is completely consistent with that of the standard NFP phase (PDF#89-0816), indicating that the sample is NFP. Fig. 9The sample obtained in Example 8 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge-discharge curves of the first three cycles show that the first cycle discharge capacity is 82.1 mAh g -1 .
[0038] Example 9 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4 were prepared in a molar ratio of 5:10:9.4:0.45, the amount of citric acid added was 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4, and the amount of urea added was 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-C6FN. Figure 1 This is the XRD pattern of the sample prepared in Example 9. It can be seen that the XRD pattern of the sample obtained in Example 9 is basically consistent with the standard NFP phase (PDF#89-0816), indicating that the main phase of the sample is NFP. Fig.10 The sample obtained in Example 9 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the first cycle discharge capacity is 135.5 mAh g -1 .
[0039] Example 10 Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4 were prepared in a molar ratio of 5:10:9.1:0.675, the amount of citric acid added was 10% of the total mass of sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate and NaBF4, and the amount of urea added was 50% of the mass of citric acid. They were ball-milled in anhydrous ethanol for 5 h (speed of 400 rpm), dried and calcined at 300 °C for 4 h (N2 atmosphere), and then calcined at 600 °C for 12 h (N2 atmosphere) to obtain NFP / C-C9FN. Figure 1 This is the XRD pattern of the sample prepared in Example 10. It can be seen that the sample obtained in Example 10 has some characteristic peaks at 12.6° and 30.1°, and the characteristic peaks at 26.6°, 32.8°, 33.0°, 34.7°, 35.5°, etc. are consistent with those of the standard NFP phase (PDF#89-0816), indicating that the main phase of the sample is NFP. Fig.11 The sample obtained in Example 10 was charged at 0.1 C (1 C = 155 mAh g -1 ) The charge and discharge curves of the first three cycles show that the first cycle discharge capacity is as high as 150.6 mAh g -1 .
Claims
1. A method for preparing a F and N co-doped NaFePO4 / C electrode material, characterized in that: Sodium carbonate, ferrous oxalate, ammonium dihydrogen phosphate, citric acid, a N source and a F source are uniformly mixed, a solvent is added and ball milled, and after drying, the mixture is calcined in two steps in a protective atmosphere to prepare a F, N co-doped NaFePO4 / C electrode material.
2. The method for preparing the F and N co-doped NaFePO4 / C electrode material according to claim 1, characterized in that: The molar percentage of the selected F source in diammonium phosphate is 1-10%, and the molar percentage of the selected N source in the total mass of sodium carbonate, ferrous oxalate, diammonium phosphate and the F source is 5-15%.
3. The method for preparing the F and N co-doped NaFePO4 / C electrode material according to claim 1, characterized in that: The N source is selected from urea; the F source is selected from any one of ammonium fluoride, sodium fluoride and sodium tetrafluoroborate.
4. The method for preparing the F and N co-doped NaFePO4 / C electrode material according to claim 1, characterized in that: In the step, the ball mill speed is 350-400 rpm, and the ball milling time is 3-5 h.
5. The method for preparing the F and N co-doped NaFePO4 / C electrode material according to claim 1, characterized in that: In the first step, the sintering temperature is 300-350°C and the time is 3-6 h, and the second step, the sintering temperature is 600-650°C and the time is 10-14 h.
6. The method for preparing the F and N co-doped NaFePO4 / C electrode material according to claim 1, characterized in that: The molar ratio of sodium carbonate to ferrous oxalate is 1:2-3.
7. A F and N co-doped NaFePO4 / C electrode material, characterized in that: The F and N co-doped NaFePO4 / C electrode material prepared by the method described in any one of claims 1 to 6 has peaks at characteristic positions of about 12.6°, 26.6°, 30.1°, 32.8°, 33.0°, 34.7°, and 35.5° in the XRD diffraction spectrum.
8. A F and N co-doped NaFePO4 / C electrode sheet, characterized in that: The F and N co-doped NaFePO4 / C electrode material according to claim 7 is stirred with acetylene black and polyvinylidene fluoride into slurry, coated on aluminum foil, and then dried, punched and pressed to make the slurry.
9. A positive electrode material, characterized in that: It includes the F and N co-doped NaFePO4 / C electrode material as described in claim 7.
10. A sodium ion battery positive electrode material, characterized in that: It includes the F and N co-doped NaFePO4 / C electrode material as described in claim 7.
Citation Information
Patent Citations
Preparation method for positive electrode material NaFePO4 / C of sodium ion battery
CN105845974A
Ferric sodium phosphate composite anode material, and preparation method and application thereof
CN109449417A
Carbon-coated sodium ferrous fluorophosphate positive electrode active material, preparation thereof and application of carbon-coated sodium ferrous fluorophosphate positive electrode active material in sodium ion battery
CN114122311A
Preparation method of sodium ferric fluorophosphate positive electrode material
CN114906832A
Cited By
Sodium ferric fluorophosphate positive electrode material with wide interlayer spacing and two-dimensional lamellar structure and preparation method of sodium ferric fluorophosphate positive electrode material
CN121035204A